Vegetable Production [brumdec] review and proposed Short-term Adaptive Production Oriented Research Programme - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
96 Páginas. Series Miscellaneous Publication N. 320.